2023
DOI: 10.1002/ccr3.7007
|View full text |Cite
|
Sign up to set email alerts
|

An overview of CYP27B1 enzyme mutation and management: A case report and review of the literature

Abstract: Vitamin D‐dependent rickets type 1 (VDDRIA) is an autosomal recessive disorder caused by mutations in the Cytochrome P450 Family 27 Subfamily B Member 1 (CYP27B1) gene, which encodes for the enzyme 1 alpha‐hydroxylase. We report a known case of VDDRIA with hypotonia, growth and developmental disorders and discuss about the mutation and its management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In this context, several studies demonstrated that mutations in three CYP genes ( CYP7A1 , CYP7B1 , and CYP27A1 ) affect bile acid synthesis and cholesterol homeostasis, with different phenotypes leading to metabolic pathologies [ 46 , 47 , 48 , 49 , 50 , 51 ]. Defects in CYPs 2R1 and 27B1, involved in the conversion of vitamin D into its physiologically active form, are genetic causes of rickets [ 52 , 53 , 54 , 55 ]. Deficiency in the retinoic acid-metabolizing enzymes from the CYP26 family is associated with skeletal and craniofacial anomalies [ 56 , 57 ].…”
Section: The Cyp Enzyme Complexmentioning
confidence: 99%
“…In this context, several studies demonstrated that mutations in three CYP genes ( CYP7A1 , CYP7B1 , and CYP27A1 ) affect bile acid synthesis and cholesterol homeostasis, with different phenotypes leading to metabolic pathologies [ 46 , 47 , 48 , 49 , 50 , 51 ]. Defects in CYPs 2R1 and 27B1, involved in the conversion of vitamin D into its physiologically active form, are genetic causes of rickets [ 52 , 53 , 54 , 55 ]. Deficiency in the retinoic acid-metabolizing enzymes from the CYP26 family is associated with skeletal and craniofacial anomalies [ 56 , 57 ].…”
Section: The Cyp Enzyme Complexmentioning
confidence: 99%